PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP KUALITAS LAPORAN KEUANGAN PERUSAHAAN NON KEUNGAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Pertiwi, Dinal Eka (UNIB Press, 2019)
This study aims to prove the effect of audit committee characteristics on the quality of financial statements and prove that audit quality affects and strengthens the relationship between audit committee characteristics and the quality of financial statements.The population of this study was non-financial companies listed on the Indonesia Stock Exchange. The selection sample was done by purposive sampling method based on inclusion criteria. Hypothesis testing in this research used linear regression analysis.The results showed that there was no association between the audit committee characteristics with persistence, predictability, the number of the audit committee expertise, and the number of the audit committee meeting. Furthermore, the commissioner independent had an effect on conservatism. The number of the audit committee expertise and the number of the audit committee meeting with the financial report timeline were correlated. In addition, big four as moderation had an association with the audit committee meeting number and conservatism, which had a big impact on strengthening the correlation between the number of the audit committee meeting and conservatism.